М.І. ДЕМКОВ ПРО ПРИНЦИПИ ВИХОВАННЯ (Педагогіка вищої та середньої школи, 2004)
The author examines the views of M.I.Demkov, a representative of the national pedagogics at the end of the XIX c. Beginning of the rote, as for the process of upbringing.